Benchmarking palliative care practices in neurooncology: a german perspective - Lawson McLean, Anna; Lawson McLean, Aaron; Ernst, Thomas; Forster, Marie-Therese; Freyschlag, Christian F.; Gempt, Jens; Goldbrunner, Roland; Grau, Stefan; Jungk, Christine; Oorschot, Birgitt van; Rosahl, Steffen K.; Wedding, Ulrich; et al. (Journal of neuro-oncology, 2024)
PURPOSE: To benchmark palliative care practices in neurooncology centers across Germany, evaluating the variability in palliative care integration, timing, and involvement in tumor board discussions. This study aims to identify gaps in care and contribute to the discourse on optimal palliative care strategies. - METHODS: A survey targeting both German Cancer Society-certified and non-certified university neurooncology centers was conducted to explore palliative care frameworks and practices for neurooncological patients. The survey included questions on palliative care department availability, involvement in tumor boards, timing of palliative care integration, and use of standardized screening tools for assessing palliative burden and psycho-oncological distress. - RESULTS: Of 57 centers contacted, 46 responded (81% response rate). Results indicate a dedicated palliative care department in 76.1% of centers, with palliative specialists participating in tumor board discussions at 34.8% of centers. Variability was noted in the initiation of palliative care, with early integration at the diagnosis stage in only 30.4% of centers. The survey highlighted a significant lack of standardized spiritual care assessments and minimal use of advanced care planning. Discrepancies were observed in the documentation and treatment of palliative care symptoms and social complaints, underscoring the need for comprehensive care approaches. - CONCLUSION: The study highlights a diverse landscape of palliative care provision within German neurooncology centers, underscoring the need for more standardized practices and early integration of palliative care. It suggests the necessity for standardized protocols and guidelines to enhance palliative care's quality and uniformity, ultimately improving patient-centered care in neurooncology.